Protein Engineering Allows for Mild Affinity-based Elution of Therapeutic Antibodies. Issue 18 (14th September 2018) - Kanje, Sara; Venskutonytė, Raminta; Scheffel, Julia; Nilvebrant, Johan; Lindkvist-Petersson, Karin; Hober, Sophia
Abstract: Presented here is an engineered protein domain, based on Protein A, that displays a calcium-dependent binding to antibodies. This protein, ZCa, is shown to efficiently function as an affinity ligand for mild purification of antibodies through elution with ethylenediaminetetraacetic acid. Antibodies are commonly used tools in the area of biological sciences and as therapeutics, and the most commonly used approach for antibody purification is based on Protein A using acidic elution. Although this affinity-based method is robust and efficient, the requirement for low pH elution can be detrimental to the protein being purified. By introducing a calcium-binding loop in the Protein A-derived Z domain, it has been re-engineered to provide efficient antibody purification under mild conditions. Through comprehensive analyses of the domain as well as the ZCa –Fc complex, the features of this domain are well understood. This novel protein domain provides a very valuable tool for effective and gentle antibody and Fc-fusion protein purification. Graphical abstract: Unlabelled Image Highlights: Widespread use of antibodies in research and therapy demands robust purification. Acidic elution is a major drawback of current Protein A-based strategies. A novel method was developed using an engineered Ca 2 + -dependent affinity ligand. The new ligand, ZCa, allows antibody purification under significantly milder conditions. A three-dimensional structure of the complex, ZCa and Fc, provides a molecular understanding.